Fabrication of porous metal by selective laser melting as catalyst support for hydrogen production microreactor. (1st January 2020) - Liu, Jie; Gao, Yu; Fan, Yanbin; Zhou, Wei
Abstract: To improve the hydrogen production performance of microreactors, the selective laser melting method was proposed to fabricate the porous metals as catalyst supports with different pore structures, porosities, and materials. The influence of the porous structures on the molecule distribution after passing through the porous metals was analyzed by molecular dynamics simulation. The developed porous metals were then used as catalyst supports in a methanol steam reforming microreactor for hydrogen production. Our results show that the porosity of the porous metal had significantly influence on the catalyst infiltration and the reaction process of hydrogen production. A lower degree of catalyst infiltration of the porous metal was obtained with lower porosity. A copper layer-coated stainless-steel porous metal with a staggered structure and gradient porosity of 80%–60% exhibited much larger methanol conversion and H2 flow rate due to its better heat and mass transfer characteristic. Methanol conversion and H2 flow rates could reach 97% and 0.62 mol/h, respectively. Finally, it was found that the experimental results were in good agreement with the simulation results. Graphical abstract: Image 1 Highlights: Porous metals are fabricated via SLM(Selective Laser Melting). Parametric modeling of controllable structure and porosity. Effects of structure, porosity and materials on hydrogen production performance. Better hydrogen production performance is obtained for porous metal with gradient porosity.